Bioreactor Systems for Tissue Engineering II 2009
DOI: 10.1007/10_2009_15
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Derived from Human Umbilical Cord Tissues: Primitive Cells with Potential for Clinical and Tissue Engineering Applications

Abstract: Mesenchymal stem or stromal cells (MSCs) have a high potential for cell-based therapies as well as for tissue engineering applications. Since Friedenstein first isolated stem or precursor cells from the human bone marrow (BM) stroma that were capable of osteogenesis, BM is currently the most common source for MSCs. However, BM presents several disadvantages, namely low frequency of MSCs, high donor-dependent variations in quality, and painful invasive intervention. Thus, tremendous research efforts have been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 100 publications
1
37
0
1
Order By: Relevance
“…Since then, authors have searched for alternative sources of MSCs because of the limited number of MSCs in bone marrow (0.001-0.01%) [Majumdar et al, 2000], the differences among patients and the invasiveness of the current bone marrow collection techniques [Moretti et al, 2010]. Many groups have compared MSCs from bone marrow and other tissues, such as adipose tissue, skin, placenta, thymus, synovium, muscle, heart, umbilical cord and vocal cords [De Ugarte et al, 2003;Musina et al, 2005;Sakaguchi et al, 2005;Wagner et al, 2005;Riekstina et al, 2009;Hanson et al, 2010;Moretti et al, 2010]. It is, therefore, necessary to determine whether MSCs from different tissues have phenotypic and differentiation potentials that are similar to bone marrow-derived MSCs [Gronthos et al, 2001;De Ugarte et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, authors have searched for alternative sources of MSCs because of the limited number of MSCs in bone marrow (0.001-0.01%) [Majumdar et al, 2000], the differences among patients and the invasiveness of the current bone marrow collection techniques [Moretti et al, 2010]. Many groups have compared MSCs from bone marrow and other tissues, such as adipose tissue, skin, placenta, thymus, synovium, muscle, heart, umbilical cord and vocal cords [De Ugarte et al, 2003;Musina et al, 2005;Sakaguchi et al, 2005;Wagner et al, 2005;Riekstina et al, 2009;Hanson et al, 2010;Moretti et al, 2010]. It is, therefore, necessary to determine whether MSCs from different tissues have phenotypic and differentiation potentials that are similar to bone marrow-derived MSCs [Gronthos et al, 2001;De Ugarte et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Pioneer works of several groups during the last decade demonstrated that the tissues of the UC harbor MSC populations exhibiting potential for clinical applications (reviewed in Ref. 22 ). Low level of rejection was observed in transplantation studies in animals [23][24][25][26] and first reports strongly suggest that MSC derived from UC display similar immunoprivileged properties 27-29 as described for BMSC.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing data, comparing the differentiation potential of MSC, should be carefully interpreted, as further studies must be performed to elucidate the differentiation capacity of MSC from different sources and to understand the involved pathways and processes [110]. In addition, a detailed understanding of the behavior and homing of MSC in vivo is required before MSC can be considered for clinical applications as safe therapeutics [111].…”
Section: Discussionmentioning
confidence: 99%